Perkembangan Pengelolaan Limbah Medis Pada Rumah Sakit - Mirzatul Nikmah; Nada Vidyan Safira; Nia Selviana Puji Lestari; Najwa Sekar Ayu Nanda Asvianto; Denny Oktavina Radianto (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Medical waste management is an important aspect of the modern health system to reduce its negative impact on the environment and human health. This article reviews various aspects of medical waste management, including the collection, processing and final disposal processes. Medical waste is collected from various health facilities, including hospitals, clinics, medical laboratories and doctors' practices. Waste management starts at the source, by separating hazardous and non-hazardous waste to ensure proper handling according to its characteristics. This process requires the use of special containers and staff training to ensure safety and compliance with applicable regulations. Awareness of the importance of safe medical waste management is increasing, with health organizations and governments working to improve regulations and educate the public about responsible practices. In a global context, international cooperation is key in overcoming the challenges of managing medical waste effectively. Thus, medical waste management is not only the responsibility of individuals or institutions, but is a joint effort to maintain environmental and community health.